The characteristics of patients frequently tested and repeatedly infected with Chlamydia trachomatis in Southwest Limburg, the Netherlands - Juliën N. A. P. Wijers; Nicole H. T. M. Dukers-Muijrers; Christian J. P. A. Hoebe; Petra F. G. Wolffs; Geneviève A. F. S. van Liere (BMC, 2020)
Abstract Background Repeat Chlamydia trachomatis (CT) infections are common. To better understand the characteristics of patients frequently infected with CT at our sexually transmitted infection (STI) care services, we assessed the differences between patients repeatedly infected with CT and those who repeatedly tested negative. Methods In this cross-sectional analysis of cohort data, we assessed individuals tested for CT at different STI care providers between 2011 and mid-2018 in Southwest Limburg, the Netherlands (n = 17,616). Patients with ≥2 repeat CT infections in the study period were categorized as "patients with repeat CT infections." Multivariable logistic regression analyses were performed for the binary outcome measure: patients with repeat CT infections versus patients who repeatedly tested negative (reference group). Additional analyses were performed for only the STI clinic population. Results Patients aged < 25 years (OR: 1.83; 95%CI:1.38-2.43), co-infected with HIV (OR: 2.07; 95%CI: 1.02-4.22) or co-infected with Neisseria gonorrhoeae (NG) (OR: 5.04; 95%CI: 3.33-7.63) had more repeat CT infections. In additional analyses among exclusively STI clinic visitors, patients with urogenital symptoms (OR: 2.17; 95%CI: 1.41-3.35), and patients notified for STIs (OR: 4.55; 95%CI: 3.17-6.54) had more frequent repeat CT infections. Conclusions Patients aged < 25 years and patients coinfected with HIV or NG had more frequent repeat CT infections, accounting for ~ 20% of the diagnosed CT infections. These patients are likely at the highest risk for transmitting and acquiring CT. Therefore, testing and retesting this group remains important to enhance CT control.